Energy conversion capacity of barium zirconate titanate - Binhayeeniyi, Nawal; Sukwisute, Pisan; Nawae, Safitree; Muensit, Nantakan (My University, 2020)
In this study, we investigated the effect of zirconium content on lead-free barium zirconate titanate (BZT) (Ba(ZrxTi1-x)O3, with x = 0.00, 0.01, 0.03, 0.05, and 0.08), which was prepared by the sol-gel method. A single-phase perovskite BZT was obtained under calcination and sintering conditions at 1100 °C and 1300 °C. Ferroelectric measurements revealed that the Curie temperature of BaTiO3 was 399 K, and the transition temperature decreased with increasing zirconium content. At the Curie temperature, Ba(Zr0.03Ti0.97)O3 with a dielectric constant of 19,600 showed the best performance in converting supplied mechanical vibration into electrical power. The experiments focused on piezoelectric activity at a low vibrating frequency, and the output power that dissipated from the BZT system at 15 Hz was 2.47 nW (30 MΩ). The prepared lead-free sol-gel BZT is promising for energy-harvesting applications considering that the normal frequencies of ambient vibration sources are less than 100 Hz.
Keywords: Barium zirconate titanate; Dielectric property; Lead-free ceramic; Sol-gel process